PSYCHOLOGICAL ATTRIBUTES AND WORK INSTABILITY IN MS. Issue 11 (14th October 2015) - Wicks, C R; Ward, Karl; Stroud, Amanda; Tennant, Alan; Ford, Helen
Abstract : For people with MS (PWMS) the relationship between job retention and psychological factors is unclear. This may lead to psychological interventions to aid job retention. This study aims to investigate relationships between psychological factors, work instability and MS in a longitudinal prospective study of PWMS in paid employment. Participants completed two time point questionnaire packs of validated scales with repeat testing planned. 221 employed PWMS were recruited. Mean age was 40.6; 75.1% were female. 91% had relapsing-remitting MS (RRMS). 213 (96.4%) completed the baseline questionnaire, 199 completed month 8. Disease progression was mostly stable with just 3% transitioning from RRMS. 57.2% were at medium/high risk of job loss, with only marginal changes in work instability at 8 months. 14% reported high physical and psychological impact of MS at baseline which remained unchanged. There was a strong association between risk of job loss and both physical and psychological variables. Some psychological variables fluctuated, e.g. depression fell from 24.6% to 14.5%. No changes were reported in levels of fatigue or pain over this period. Psychological attributes in MS appear to fluctuate but contribute to work instability. Further investigation will clarify this relationship and inform possible intervention strategies.